2017
DOI: 10.5194/isprs-archives-xlii-4-w5-127-2017
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapour Weighted Mean Temperature Model for GPS-Derived Integrated Water Vapour in Peninsular Malaysia

Abstract: ABSTRACT:This paper presents the development of T M model by using the radiosonde stations from Peninsular Malaysia. Two types of T M model were developed; site-specific and regional models. The result revealed that the estimation from site-specific model has small improvement compared to the regional model, indicating that the regional model is adequately to use in estimation of GPS-derived IWV over Peninsular Malaysia. Meanwhile, this study found that the diurnal cycle of T S has influenced the T M -T S rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In Musa et al (2017) authors revealed that PWV measurements from both the regression line (Tm -Ts) exhibit a high degree of agreement. Tm and Ts are warm throughout the year, with just a 1.0 -2.0 K fluctuation.…”
Section: Comparison Of Tm Calculationmentioning
confidence: 95%
“…In Musa et al (2017) authors revealed that PWV measurements from both the regression line (Tm -Ts) exhibit a high degree of agreement. Tm and Ts are warm throughout the year, with just a 1.0 -2.0 K fluctuation.…”
Section: Comparison Of Tm Calculationmentioning
confidence: 95%